2021
DOI: 10.3389/fpubh.2021.629236
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evidence Assessment of Mental Health Outcomes of Pandemics for Health Care Workers: Implications for the Covid-19 Pandemic

Abstract: Background: Little is known about the long-term mental health (MH) impact of the Covid-19 pandemic on health care workers (HCWs). However, synthesizing knowledge from past pandemics can help to anticipate this, along with identifying interventions required, when, and target populations most in need. This paper provides a balanced evaluation of what is currently known about short- and long-term MH impacts of pandemics on HCWs and effect of methodological limitations on knowledge claims.Method: A rapid evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 71 publications
2
6
0
Order By: Relevance
“…23,24 Healthcare professionals or decision-makers reported experiencing ''change fatigue'' due to the reported frequent changes to COVID-19-related policies and procedures 25,26 and distress when a patient's family could not be present at the bedside at the end of life. [27][28][29] Aligned with research showing that the COVID-19 pandemic affected the mental health of the general public and front-line healthcare professionals, [30][31][32][33][34][35][36] we found that participants shared similar experiences including change fatigue and psychological and emotional distress. As such, final consensus statements should be succinct and engage multidisciplinary stakeholders, and their implementation should be minimally burdensome.…”
Section: Discussionsupporting
confidence: 62%
“…23,24 Healthcare professionals or decision-makers reported experiencing ''change fatigue'' due to the reported frequent changes to COVID-19-related policies and procedures 25,26 and distress when a patient's family could not be present at the bedside at the end of life. [27][28][29] Aligned with research showing that the COVID-19 pandemic affected the mental health of the general public and front-line healthcare professionals, [30][31][32][33][34][35][36] we found that participants shared similar experiences including change fatigue and psychological and emotional distress. As such, final consensus statements should be succinct and engage multidisciplinary stakeholders, and their implementation should be minimally burdensome.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies show the key role that organizations and public health bodies play in promoting adaptive coping and reducing health worries and the emotional and psychological distress caused by the pandemic. Evidence highlights particular groups at risk of developing mental health problems (contact with infected patients, having children), and time points where risk may increase (initial response phase, when quarantined) [58]. Our study raises three main implications for public and global health in Peru and other Low and Middle-Income Countries (LMIC) with similar characteristics.…”
Section: Implications In Public Health and Making Decisionsmentioning
confidence: 78%
“…Regarding gender and mental health, several studies highlighted gender differences in the psychological outcomes of HCWs [14,45]. These findings had mixed results, but our result was consistent with studies from China [46,47] that men had a greater chance of depersonalisation, lack of personal achievement, anxiety and PTSD.…”
Section: Discussionsupporting
confidence: 85%